Emended description and new localities of Oxygyne shinzatoi (Burmanniaceae/Thismiaceae), with discussion of phylogenetic relationships of Oxygyne from Japan and Africa - Suetsugu, Kenji; Sugimoto, Takaomi; Tsukaya, Hirokazu (Phytotaxa, 2019)
During a recent survey, Oxygyne specimens were discovered in three lowland evergreen forests on Okinawa Island, Japan. After morphological investigation, we identified the specimens as O. shinzatoi. Intriguingly, the colour of the specimens from one of the localities was significantly different from that of specimens collected from both the type and two of the new localities. Furthermore, morphological analysis also revealed clear differences between specimens collected from the type locality, including the type specimen, and previous descriptions of O. shinzatoi. Therefore, an amended description of O. shinzatoi is provided, based on the type and newly collected specimens. Phylogenetic relationships of Oxygyne from Japan and western Central Africa are also discussed, with consideration of the characteristics of newly discovered colour variation.